2018
DOI: 10.1097/jom.0000000000001416
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Job Stressors and Mental Health

Abstract: Individual differences in emotion regulation in response to adverse job conditions should be considered in the management of workplace mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Taken together, daily FoMO appeared to be less strongly associated with lower daily affective well-being among participants who had higher tendencies to engage in cognitive reappraisal relative to their counterparts. Indeed, this finding is consistent with previous studies that showed cognitive reappraisal as an effective strategy in managing one’s negative emotions in response to emotionally threatening situations (Shapero et al, 2019; Too & Butterworth, 2018; Troy et al, 2010). Moreover, it is unlikely that this moderation effect was driven by multicollinearity issues; i.e., lower levels of FoMO, to begin with, among individuals who frequently utilize cognitive reappraisal (Shieh, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Taken together, daily FoMO appeared to be less strongly associated with lower daily affective well-being among participants who had higher tendencies to engage in cognitive reappraisal relative to their counterparts. Indeed, this finding is consistent with previous studies that showed cognitive reappraisal as an effective strategy in managing one’s negative emotions in response to emotionally threatening situations (Shapero et al, 2019; Too & Butterworth, 2018; Troy et al, 2010). Moreover, it is unlikely that this moderation effect was driven by multicollinearity issues; i.e., lower levels of FoMO, to begin with, among individuals who frequently utilize cognitive reappraisal (Shieh, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…They will think about the events that make them feel bad in a less favorable or accepting way; they experience more negative emotions than those who use suppression less. Some studies show that when facing a state of high-stress, if individuals use expressive suppression more frequently, they tend to feel burnout [39], and this aggravates their negative feelings [35]. Moore et al [40] found that expressive suppression is often positively correlated with stress-related symptoms, such as post-traumatic stress disorder, anxiety, and depression.…”
Section: The Mediation Role Of Parents' Expressive Suppressionmentioning
confidence: 99%
“…Although individuals may face the same stressful event (for example COVID-19) there are individual differences in how associated negative emotions are experienced or regulated ( Gross and John, 2003 ; Too and Butterworth, 2018 ; Raymond et al, 2019 ). Recent studies found that during the COVID-19 pandemic, several resources and resilience factors played moderating and/or mediating roles in the associations between stressful experiences and mental health, e.g., individuals’ sense of meaning of life ( Schnell and Krampe, 2020 ), locus of control ( Krampe et al, 2021 ), psychological flexibility ( Smith et al, 2020 ), personality traits ( Bacon and Corr, 2020 ; Smith et al, 2020 ; Liu et al, 2021 ; Abdelrahman, 2022 ; Lassen et al, 2022 ), as well as emotion regulation abilities ( Xu et al, 2020 ; Liang et al, 2021 ; Ye et al, 2021 ; Gullo et al, 2022 ; Vertsberger et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%